Intervensi kelompok coloring mandala untuk gangguan kecemasan menyeluruh di panti rehabilitasi ”b”, Jawa Tengah - Lakaseru, Angelica Pradita Adelide (Jurnal Psikologi Poseidon, 2025)
Anxiety is a feeling of fear that is unclear and not supported by a certain situation that if not handled properly, can interfere with several aspects of a person's life such as social life, work, and physical disorders. Coloring Mandala is one of the art therapy techniques that can reduce anxiety levels. This intervention aims to reduce anxiety levels through group therapy coloring mandala. This intervention was carried out in a group of 5 people who experienced anxiety symptoms (1 male and 4 females) for at least 1 month. Assessment of anxiety levels before and after the intervention used DASS 42-A and interviews. To see the difference in the results of the pre-test and post-test intervention, a paired sample T-test was conducted using JASP Software. Based on the results of the statistical test, it was obtained that the level of anxiety after the group intervention (M = 11.6; SD = 5.771) was significantly lower than before the group intervention (M = 26.6; SD = 7.701) t (4) = 7.798, p = 0.001. The interview results also showed changes before and after the intervention such as the emergence of positive thoughts, reduced physical complaints, and a positive atmosphere within the group. The results showed that the coloring mandala intervention could significantly reduce anxiety levels in adults at the "B" Rehabilitation Center who experienced generalized anxiety disorder.